2017
DOI: 10.1002/1873-3468.12882
|View full text |Cite
|
Sign up to set email alerts
|

Ecm33 is a novel factor involved in efficient glucose uptake for nutrition‐responsive TORC1 signaling in yeast

Abstract: Glucose uptake is crucial for providing both an energy source and a signal that regulates cell proliferation. Therefore, it is important to clarify the mechanisms underlying glucose uptake and its transmission to intracellular signaling pathways. In this study, we searched for a novel regulatory factor involved in glucose-induced signaling by using Saccharomyces cerevisiae as a eukaryotic model. Requirement of the extracellular protein Ecm33 in efficient glucose uptake and full activation of the nutrient-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…For glucose restriction, cells were grown in YP medium containing 2 % glucose until the early stage of growth, before shifted to YP medium containing 0.05 % glucose for 5 h. At the indicated time points, cells were collected and total protein extracts were precipitated with trichloroacetic acid-acetone method as we described previously. 12) 13) The protein amount of Emi2-GFP was monitored by immunoblotting using anti-GFP antibody (sc-9996) (Santa Cruz Biotechnology, TX, USA). The endogenous tubulin was monitored as a loading control using anti-alpha Tubulin antibody (ab-184970) (Abcam, CB, UK).…”
Section: Methodsmentioning
confidence: 99%
“…For glucose restriction, cells were grown in YP medium containing 2 % glucose until the early stage of growth, before shifted to YP medium containing 0.05 % glucose for 5 h. At the indicated time points, cells were collected and total protein extracts were precipitated with trichloroacetic acid-acetone method as we described previously. 12) 13) The protein amount of Emi2-GFP was monitored by immunoblotting using anti-GFP antibody (sc-9996) (Santa Cruz Biotechnology, TX, USA). The endogenous tubulin was monitored as a loading control using anti-alpha Tubulin antibody (ab-184970) (Abcam, CB, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that TORC1, which is at least partly synchronized with PKA/Snf1, regulates autophagy as well as the Ams1 activity . We next thought to determine whether deletion of CLB4 affects TORC1 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we asked whether disruption of Clb4 causes dysregulation of autophagy. As well as Ams1 activity, autophagy is suppressed under nutrient‐rich conditions but induced by glucose starvation through the activity of the TORC1 and PKA/Snf1 pathways . To quantify the magnitude of autophagy, we utilized the GFP‐Atg8 processing assay, according to reported procedures .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations